Arabic and Islam in the Globalization Era - Fahmi Sofyan; Anshar Zulhelmi; Zulkhairi; Zulhelmi; Badat Alauddin; Akmal Fajri (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article presents the relation between Arabic, Islam, and globalization. It highlighted the challenges faced by globalization to Islamic and Arabic identities. The research aimed to explore how modern technological advancements, particularly in information and communication technologies (ICT) and artificial intelligence (AI), can be utilized to revitalize Islamic and Arabic studies. A qualitative methodology was employed, drawing on Islamic theological texts, historical scholarship, and recent trends in AI and ICT. The results showed that ICT, including the internet, mobile devices, and social media, plays a crucial role in transforming communication, education, and scholarship. It enables the dissemination of Islamic knowledge globally and provides new platforms for linguistic and theological engagement. Furthermore, the study examined how AI, when applied within an ethical Islamic framework, can contribute to human well-being, particularly in sectors like healthcare, by preserving life and promoting justice. The research also underscored the necessity of renewing Arabic linguistic studies to ensure they adapt to modern learning methods, such as e-learning and AI-enhanced teaching tools. The study concluded by emphasizing that the ethical integration of AI in Islamic and Arabic studies offered significant opportunities for cultural and intellectual renewal, ensuring the relevance of these fields in the digital age while preserving Islamic principles.